WAWASAN AL-QUR’AN TENTANG RADIKALISME DAN PENANGANANNYA DI ERA MILENIAL - Nurasih, Wiji (IAIN Purwokerto, 2019)
This paper seeks to examine the insights of the Qur’an about radicalism and how to deal with it in the millennial era by utilizing information technology to realize moderate Islam. At present the notion of radicalism has spread through various means and has become a troubling problem. This needs to be dealt with seriously in order to realize peace and tranquility in life throughout the world. Al-Qur’an as a way of life for Muslims also contains things about the problems of mankind, instructions for their settlement and so forth. So in this paper we will examine how the Qur’an talks about radicalism and seek solutions to these problems. Data sources were obtained through literature review and explained descriptively analytically. The study was conducted through a review of several interpretations of the Qur’an and other supporting sources. From this study, the results show that human radical behavior that occurs among humans has been described in Surat al-Baqarah verse 30. Then in this verse also Allah SWT states that he will make a caliph on earth. Departing from this verse, the author tries to contextualize it now so that the millennial generation can play a role in addressing and overcoming the phenomenon of radicalism by utilizing information technology in accordance with the guidance of the Qur’an